PREDIKSI SEBARAN SISTEM PENGELOLAAN SAMPAH PADA TAHUN 2030 DENGAN PENDEKATAN SIG (SISTEM INFORMASI GEOGRAFIS) (STUDI KASUS: PULAU SUMATERA) - Fajriharish Nur Awan; Radhitiya Al Furqan (Ensiklopedia of Journal, 2021)
Sumatra has the second largest population after Java, which is about 22% of the population in Indonesia resides on the Sumatra. The increase in population greatly affects the amount of waste generated every time, so that the Sumatra is one of the regions of Indonesia that is very influential in the increase in waste generation in Indonesia. The generation of rural waste on the Sumatra is still around 6% that is transported and the generation of urban waste on the Sumatra is still at the figure of 45% that is transported. Based on some of these problems, it is still far from the target of SDGs 2030 and RPJMN 2020-2024, which is achieving 100% of managed waste. So there is a need for a study to determine the prediction of the distribution of the waste management system in 2030 on the Sumatra. The outputs that will be produced in this study include a prediction map of the distribution of the waste management system in 2030 and the investment costs required for development as well as direct and indirect benefit costs. The methods used in this study include population projection, overlay, and grid methods. The determination of the waste management system is determined based on population density, adjustments to the TPA which ends operating before 2030, and the adjustment of the TPS 3R and TPA development targets based on the 2020-2024 RPJMN. The prediction results of the waste management system on the Sumatra are still dominated by 3R Individuals, because the dominant population density is <25 people/ha. Of the 4 provinces that have been described, the predictions of TPS 3R and TPA are in cities with a population density of 25<X<100 people/ha.Keywords: waste management system, Sumatra Island, prediction.